Institutional Quality and Tax Capacity: Evidence from SAARC Countries - Altaf, Umar; Zameer, Sahrish; Muhammad Sohail Akhtar (iRASD Journal of Economics, 2024)
Analyzing the impact of institution quality on tax capacity across the seven SAARC nations is the study's primary goal. Data on tax income, institutional quality, and other associated variables from 1996 to 2020 are gathered for this purpose by the study. To empirically estimate the results the study first applies the pre-estimation test like the unit root test, cointegration test, and slope heterogeneity test. The results of these tests indicate that variables have a mixed order of integration, the long-run relationship exists among the variables and slopes are heterogeneous across the cross-section units. Finally, the study applies the fixed effect model and PMG model. The estimated results from the fixed effect model indicate that institutional quality significantly and positively influences tax capacity. Furthermore, the PMG model's findings show that institutional quality eventually and favorably increases tax capacity. There are also some control factors in the study. Population, GDP per capita growth rate, and gross capital formation—the control variables—all exhibit a statistically significant positive correlation with tax capacity over the long term. FDI and inflation are two more control factors that have an inverse long-term relationship with tax capacity. However, these two factors have a short-term favorable impact on tax capacity. Based on the results, the study recommends that the economies' top objective should be to raise the caliber of their institutions in order to promote long-term economic growth.